Effect of Electroacupuncture at Quchi and Zusanli Acupoints on Peri-infract Striatal Neural Autophagy in MCAO Rats - Weilin LIU; Yunjiao LIN; Jing TAO (康复学报)
Objective:To observe the effects of electroacupuncture (EA) at the Quchi (LI11) and Zusanli (ST36) acupoints on peri-infract striatal neural autophagy in middle cerebral artery occlusion (MCAO) -induced ischemia and reperfusion injured rats.Methods:Thirty-six SD rats were divided into the sham group, the MCAO group and the EA group by a random number table, 12 rats in each group. After the MCAO models were established according to the Koizumi method, the rats in the EA group received EA at the LI11 and ST36 acupoints intervention with 3 days. The infract volume of cerebral ischemia were measured by TTC staining. The number of autophagosome and the structure of mitochondria were evaluated by electron microscope (EM). The expression of autophagy marker microtubule-associated protein 1ight chain 3B (LC3B) were detected.Results:TTC staining showed that the infarct volumes of rats in the EA group were reduced compared to the sham group (P<0.05). The EM showed that the number of lysosomes and autolysosome were increased in the MCAO group, and after EA intervention, the phenomenon that increased lysosomes and autolysosome was weakened compared to the MCAO group. The levels of LC3BⅡ/LC3BⅠin the EA group were increased compared to the MCAO group (P<0.05).Conclusion:In the subacute stage of cerebral ischemic injury, EA at the LI11 and ST36 acupoints could alleviate autophagic cell death induced by excessive release of lysosomes and autolysosome in peri-infract striatum, the mechanisms of which need to be studied further.